WEAPON DETECTION SYSTEM (Journal of Informatics Education and Research, 2025)
This project aims to develop a real-time weapon detection system using CCTV video to enhance public safety by detecting threats early and reducing the requirement for human monitoring. The technology will accurately detect and classify weapons in live video feeds by employing advanced deep learning algorithms, ensuring an early response to any threats. This technology will be integrated with the existing security framework to enhance overall safety protocols and speed up surveillance activities .To achieve high accuracy and low latency in weapon identification, the system will utilize advanced deep learning models, like convolutional neural networks and object recognition frameworks like YOLO or SSD. This approach fosters a more efficient and reactive security environment apart from solving the problems of the current security situation.